Local Wisdom of The Nurul Huda Pajagalan Islamic Boarding School as Strengthening Moral Values and Character Education For Students of STAI Al Musdariyah Cimahi - lia apriliani, Ai; Nurlatifah, Irma (AIM: Journal of Islamic Education Management, 2024)
Educational institutions and Islamic boarding schools are closely related, especially in developing local wisdom to create good moral values and student character. This writing is entitled "Local Wisdom of Islamic Boarding Schools as Strengthening Moral Values and Character Education for Students". This research aims to ensure that students can have better moral values and character, and can complement each other in developing attitudes and character and continuing the noble cultures of the past. The research method used is a qualitative library study method by collecting data, and reviewing references related to the theme to be researched. The results of research on moral values in Islamic boarding schools for students who have education in Islamic boarding schools include the instillation of local values and character education from local wisdom which is still being developed, namely imtihan and bandongan poetry. The moral value of having poetry in Islamic boarding schools can have a big influence on education, the poetry itself can make it easier for students to memorize the rules. And with bandongan, students will be better able to understand the material being presented. With local wisdom, it can instill the character of students to be independent and have better values in education. It turns out that the role of Islamic boarding school local wisdom in education as students in Islamic boarding schools will strengthen this role which is beneficial for students as part of a society that has high moral values, and character and also continues to foster local culture as a forum for education